Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Direktorat Jenderal Hak Asasi Manusia - Maulina Sihaloho; Wahyudin Sastramenggala; Sasli Rais (JURNAL ILMU ADMINISTRASI PUBLIK DAN BISNIS, 2020)
This study aims to find out how much influence work discipline has on improving the performance of employees of the Directorate General of Human Rights. The research was conducted at the Directorate General of Human Rights which began from January 2014 to July 2014. With simple regression analysis techniques known that Work Discipline has a significant and positive effect on Employee Performance, the amount of influence is 35.0 percent.